Drug delivery systems designed to overcome antimicrobial resistance. Issue 6 (19th April 2019) - Pham, Thanh‐Nhat; Loupias, Pauline; Dassonville‐Klimpt, Alexandra; Sonnet, Pascal
Abstract: Antimicrobial resistance has emerged as a huge challenge to the effective treatment of infectious diseases. Aside from a modest number of novel anti‐infective agents, very few new classes of antibiotics have been successfully developed for therapeutic use. Despite the research efforts of numerous scientists, the fight against antimicrobial (ATB) resistance has been a longstanding continued effort, as pathogens rapidly adapt and evolve through various strategies, to escape the action of ATBs. Among other mechanisms of resistance to antibiotics, the sophisticated envelopes surrounding microbes especially form a major barrier for almost all anti‐infective agents. In addition, the mammalian cell membrane presents another obstacle to the ATBs that target intracellular pathogens. To negotiate these biological membranes, scientists have developed drug delivery systems to help drugs traverse the cell wall; these are called "Trojan horse" strategies. Within these delivery systems, ATB molecules can be conjugated with one of many different types of carriers. These carriers could include any of the following: siderophores, antimicrobial peptides, cell‐penetrating peptides, antibodies, or even nanoparticles. In recent years, the Trojan horse‐inspired delivery systems have been increasingly reported as efficient strategies to expand the arsenal of therapeutic solutions and/or reinforce the effectiveness of conventional ATBs against drug‐resistant microbes, while also minimizing the side effects of these drugs. In this paper, we aim to review and report on the recent progress made in these newly prevalent ATB delivery strategies, within the current context of increasing ATB resistance.